The Quest for Community Development in Nigerian: An Interrogation of Autonomous Community System’s Contributions towards Rural Electrification in Ikeduru Local Government Area of IMO State - OPARA, Ikechukwu Jonathan; EZIKEUDU, Chukwudi Charles; OKORIE, Chimaobi; ODIGBO, Benedict Ejikeme; ISOKON, Brown; EBEGBULEM , Joseph Chidi; AMALU, Nneka Sophie; UNDIYAUNDEYE, Florence A.; IWARA, Iwaara Eno; ENAMHE , Dorn Cklaimz; EFFIONG, Mary; NJOKU, Raymond Amanzie; et al. (Journal of Ecohumanism, 2024)
This study examined the contributions of autonomous community system towards rural electrification in Ikeduru Local Government Area of Imo State, Nigeria. The study anchored on community development model. This study adopted mixed research design. Survey method of data gathering which involved Questionnaire and interview techniques were utilized for collection data. The researchers employed simple percentage, Kearl Pearson correlation, analysis of variance (ANOVA) and regression analysis for data presentation and analysis. The study discovered that autonomous community system in Ikeduru have made tremendous impact on rural electrification in the study area. Based on the findings of the study, the researchers recommended that autonomous community system should be empowered by the government to monitor the implementation of government projects sited in their localities, so as to ensure proper resource management, enhanced accountability and timely completion of projects and actualization of its goals.